Experts in the Boardroom: Director Connections in the Mutual Fund Industry* - Calluzzo, Paul (Contemporary Accounting Research, 2023)
ABSTRACT This study examines boardroom connections that form when corporate executives sit on mutual fund boards. These connections have the potential to facilitate information flow that informs fund investment decisions. I find that fund trades in the executive's firm anticipate future earnings news and stock returns during the period that the fund and firm are connected. The evidence is consistent with a broad scope of information being transferred through the connections, implying the potential for these connections to have an economically significant impact. For example, trades in the executive's firm predict returns both inside and outside of the earnings announcement period, and trades in stocks in the same sector as the executive's firm also predict returns. This study highlights the potential for the role of fund directors to extend beyond their formal monitoring responsibilities and act as conduits of information.